Luteoloside inhibiting the prostate cancer cells growth and promoting the tumor cells autophagy through AKT/mTOR pathway - Haoyue Li; Xi Wang; Aiyangzi Lu; Yongmei Pan; Wei Zhang; Lei Hao (Journal of Men's Health, 2023)
Prostate cancer (PC) is one of the prevalent tumors in men causing higher mortality. Luteoloside has been discovered for suppressive role into the progression of some cancers. However, the Luteoloside’s regulatory functions regarding PC progression are not well understood. This study is thus designed to investigate the Luteoloside impact on PC progression. In this work, it was demonstrated that the PC cell proliferation was gradually inhibited with the increasing Luteoloside dose (0, 20, 40, 80 µM). Luteoloside also enhanced the PC cell apoptosis. It promoted the autophagy in PC through increasing microtubule-associated protein light chain (LC) 3II/LC3I levels and decreasing p62 levels. Moreover, the Luteoloside reduced phosphorylated-protein kinase B (p-AKT)/AKT and phosphorylated-mechanistic target of rapamycin (p-mTOR)/mTOR levels, indicating that it retarded the AKT/mTOR pathway. In conclusion, the Luteoloside inhibited PC cells growth and promoted tumor cells autophagy through AKT/mTOR pathway. This discovery suggested the Luteoloside as a potential drug in treating PC.